THE WELFARE OF FEMALE WORKER FAMILY FROM MAQÂSHID ASY- SYARÎʻAH PERSPECTIVE (Labor Case Study in CV. Kausar Jaya, Gresik) - Anwarul Sholihin; Muhammad Ghafur Wibowo (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2017)
The impetus of women plunging into labor is to improve the quality of life and their families welfare from the wages allocated to the needs of their families. The facts on the field show that many female workers who work in large industries are not prosperous because they are not entitled as a labor, including the right to worship in accordance with their respective religions and the obligations of employers to prepare adequate praying space. The purpose of this research is to know and measure the level of welfare of female workers in CV Kausar Jaya based on the perspective of maqâshid asy-syarî'ah. The research approach used in this research is qualitative approach. Data sources were taken from interviews with workers and leaders of CV Kausar Jaya. The research results found that CV Kausar Jaya workers were given places and times to pray, timely wages, and holidays, but the workers of CV Kausar Jaya did not get the vitamins for the eyes and social security of labor. –( Dorongan perempuan terjun menjadi tenaga buruh adalah untuk meningkatkan kualitas hidup dan kesejahteraan keluarga mereka dari upah yang dialokasikan untuk kebutuhan keluarganya. Fakta di lapangan menunjukkan bahwa banyak pekerja perempuan yang bekerja di industri besar ternyata tidak sejahtera, karena mereka tidak diberi hak sebagai buruh, termasuk hak beribadah sesuai dengan agama masing-masing dan kewajiban pengusaha untuk menyiapkan ruang sholat yang memadai. Tujuan penelitian ini untuk mengetahui dan mengukur tingkat kesejahteraan pekerja wanita di CV Kausar Jaya berdasarkan perspektif maqâshid asy-syarî'ah. Pendekatan penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Sumber data diambil dari wawancara dengan pekerja dan pimpinan CV Kausar Jaya. Hasil penelitian menemukan bahwa pekerja CV Kausar Jaya diberi tempat dan waktu sholat, upah tepat waktu, dan hari libur, tetapi para pekerja CV Kausar Jaya tidak mendapatkan vitamin untuk mata dan jaminan sosial tenaga kerja.)—Keywords: Labor Welfare, Labor family welfare, Maqâshid Asy-Syarîʻah.